Stress and its relation to the alcohol and cigarette consumption of selected university students - Castro, Karina Mia L. (College of Home Economics, University of the Philippines Diliman, 2014)
This study aimed to identify the common stressors experienced by university students, the levels of stress of the stress classifications and the relation of overall stress to the cigarette and alcohol consumption of students. Purposive sampling was used to select the respondents within a university in Quezon City. They are undergraduate university students who consume both alcohol and cigarette products. Responses to the survey questionnaire generated the following information: the average amount of cigarette sticks consumed, the main reason for smoking cigarettes, the frequency of alcohol consumption, whether the respondents have consumed cigarette and alcohol products the previous day, their stressors from the previous day, and the level of stress of each stressor and of the whole day. The data gathered from the 50 respondents were subjected to frequency distribution, mean ranking, Spearman's rho and chi-square test of independence. Results show that academic and intrapersonal stressors are the most frequent stressors encountered by the respondents. Academic stressors are also deemed the most stressful among the stress classifications, followed by interpersonal stressors such as relationship and family problems. Students smoke mainly to release tension and to feel relaxed. As their levels of stress increase, their cigarette consumption also increases. Drinking is a common occurrence in college life as most students consume alcoholic beverages at least once a week. Perceived overall stress is not found to be a significant factor in the alcohol consumption of students and they drink mainly to socialize with their friends.